Effects of a breakwater on a floating solar farm in heading and oblique waves - Zou, Detai; Wei, Yujia; Ou, Binjian; Zhang, Chao; Chu, Shengnan; Huang, Luofeng (American Institute of Physics (AIP), 2024)
Floating photovoltaic (FPV) solar farms have gained significant research and industrial interest in recent years. However, to support its deployment in abundant ocean space, FPV is required to be protected against wave loading. Thus, the usage of a breakwater in front of a floating solar farm is particularly promising. In this work, a time-domain simulation model for an array of FPV solar units in heading and oblique waves was established. Following validation against experiments, the model was used to predict the wave-induced motion and loading responses of each floating solar unit in an array, first without a breakwater, and subsequently with a breakwater. By comparison, it was found that a breakwater can reduce the wave-induced motions of a floating solar farm by up to 56%, alongside up to 55% reduction of loading on the joints between FPV units. However, the breakwater is less effective in relatively long waves and could induce some increase in loading on joints, signifying future work to optimize the design of the breakwater based on the intended environmental condition. Overall, the present results provide insights into a practical breakwater solution for FPV in offshore and coastal conditions, supporting the long-term development of this industry.
Keywords: Fluids & Plasmas; 40 Engineering; 49 Mathematical sciences; 51 Physical sciences; Photovoltaics; Renewable energy; Solar panels; Wave propagation; Computational models; Fluid dynamics; Flow simulations